SAT0242 SENSITIVITY OF TEMPORAL ARTERY BIOPSY IN GIANT CELL ARTERITIS: SYSTEMATIC LITERATURE REVIEW AND META-ANALYSIS OF CLINICAL DATA. (June 2019) - Rubenstein, Emma; Maldini, Carla; Gonzalez-Chiappe, Solange; Chevret, Sylvie; Mahr, Alfred
Abstract : Background: The role of temporal artery biopsy (TAB) as a reference test for the diagnosis of giant cell arteritis (GCA) is currently questioned by the use of non-invasive imaging techniques such as temporal artery ultrasonography (TA-US). Although TAB is highly specific, a subset of patients with a clinical diagnosis of GCA does not show the characteristic histopathological signs. The lack of knowledge of the proportion of GCA cases with positive findings on TAB hampers comparisons of the sensitivity of TAB and imaging tests for diagnosing GCA. Objectives: We performed a systematic literature review and meta-analysis to estimate the sensitivity of TAB in GCA and to identify factors that may influence the estimate. Methods: We searched MEDLINE via PubMed, EMBASE and CENTRAL databases for articles reporting TAB in GCA that were published from 1990 to 2017, with no language restriction. Eligibility criteria included studies with ≥30 GCA cases fulfilling the original or modified 1990 ACR classification criteria for GCA. From eligible publications, two independent researchers extracted the main methodological, geographic, demographic, and clinical characteristics and the number of TAB-positive cases among all cases with interpretable results for TAB. By meta-analysis, we computed the pooled proportion of TAB-positive GCA cases by using a random-effects model with a binomial-normal distribution and assessed heterogeneity by the I 2 statistic. Subgroup and meta-regression analyses were used to examine the effect of 16 covariates (e.g., geographic, demographic, clinical and study descriptors) on TAB positivity. Results: Among 3820 screened publications, 32 independent studies (3092 GCA patients in total) were used for the analysis. The pooled proportion of TAB positivity was estimated at 77.3% (95% confidence interval 71.8–81.9%), with high between-study heterogeneity ( I 2 =90%). Subgroup analysis suggested a potential influence of year of publication (Table). This result was confirmed by univariate ( P =0.0008) and multivariate meta-regression ( P =0.0004). No other analyzed covariate significantly influenced the sensitivity of TAB in GCA. Conclusion: The 77% estimated sensitivity of TAB in GCA indicates that it is not inferior to that of TA-US (1). The decline in TAB-positive GCA cases over time could reflect an increasing propensity of clinicians to accept GCA diagnosis in the absence of proof by TAB. The unexplained high between-study heterogeneity could also result from differences in TAB sampling, processing or interpretation. Reference: [1] Duftner C, Dejaco C, Sepriano A, et al. Imaging in diagnosis, outcome prediction and monitoring of large vessel vasculitis: a systematic literature review and meta-analysis informing the EULAR recommendations. RMD Open. 2018;4:e000612. Disclosure of Interests: Emma Rubenstein: None declared, Carla Maldini: None declared, Solange GONZALEZ-CHIAPPE: None declared, Sylvie Chevret: None declared, Alfred Mahr Consultant for: Chugai Pharma France, Speakers bureau: Roche SAS Chugai Pharma France